2013
DOI: 10.1142/s0218348x13500126
|View full text |Cite
|
Sign up to set email alerts
|

Why Farima Models Are Brittle

Abstract: The FARIMA models, which have long-range-dependence (LRD), are widely used in many areas.Through deriving a precise characterisation of the spectrum, autocovariance function, and variance time function, we show that this family is very atypical among LRD processes, being extremely close to the fractional Gaussian noise in a precise sense. Furthermore, we show that this closeness property is not robust to additive noise. We argue that the use of FARIMA, and more generally fractionally differenced time series, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this regard, the restriction on the sum of the coefficients in the moving average representation may be too strict for real data. It takes but a small deviation on any of the infinite coefficients to violate this restriction, providing further evidence of the brittleness of fractionally differenced processes; see Veitch et al (2013). We showed that CSA(a, b) processes do not share these restrictions and are thus less brittle.…”
Section: Nonfractional Long-range Dependence and The Antipersistent Propertysupporting
confidence: 52%
See 2 more Smart Citations
“…In this regard, the restriction on the sum of the coefficients in the moving average representation may be too strict for real data. It takes but a small deviation on any of the infinite coefficients to violate this restriction, providing further evidence of the brittleness of fractionally differenced processes; see Veitch et al (2013). We showed that CSA(a, b) processes do not share these restrictions and are thus less brittle.…”
Section: Nonfractional Long-range Dependence and The Antipersistent Propertysupporting
confidence: 52%
“…Granger argued that fractionally integrated processes fall into the "empty box" category of theoretical developments that do not arise in the real economy. Moreover, Veitch et al (2013) argued that "time series whose long-range dependence scaling derives directly from fractional differencing [...] are far from typical when it comes to their long-range dependence character". Thus, this paper developed a long-range dependence framework based on cross-sectional aggregation, the most predominant theoretical explanation for the presence of long-range dependence in data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective FGN and ARFIMA processes have the same fixed point as the limit of these operations tend to infinity. However, ARFIMA processes do differ from FGN in that you could change the fixed point, i.e., alter the eventual limit under aggregation and rescaling, with the addition of additive noise [35], i.e., this class was less robust to the addition of noise. Hence, there may be some differences in behaviour when looking through an entropic lens.…”
Section: Entropy Rate Function For Arfima(pdq)mentioning
confidence: 99%